Mechanical Properties of the Mineral Cast Material at the Macro and Micro Level. - Kępczak, Norbert; Pawłowski, Witold; Klich, Marek; Kaczmarek, Łukasz (Lodz University of Technology. Faculty of Mechanical Engineering. Department Division of Dynamics., 2016)
The paper presents the results of experimental examination of the mechanical properties at micro and macro scale of the mineral cast composites. Studies have been conducted to verify the literature data about the value of tensile strength, compressive strength and Young’s modulus. Additionally as a part of this research Poisson’s ratio was determined, which has not been encountered in the current literature as deeply as in this work. In the next step, a scanning electron microscopy (SEM) studies have been carried out to analyze fractures of the samples after tensile and compression tests. These results were correlated with mechanical properties such as tensile strength and compressive strength, respectively. During fracture investigations, the contact interface between concrete filler and polymer was studied. As a result of this research the mechanism of deformation was formulated.
Keywords: mineral cast; composite; mechanical properties; microstructure; odlew mineralny; kompozyt; właściwości mechaniczne; mikrostruktura